(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The neurophysiology of emotions and psychological effects represents one of the most complex and fascinating areas of neuroscience research. This study examines the formation of neural networks underlying emotional processing and their regulatory mechanisms. Through comprehensive analysis of current neurophysiological research, we investigated the structural and functional organization of emotion-related neural circuits, including the limbic system, prefrontal cortex, and their interconnections. Our research utilized a systematic review approach, analyzing neuroimaging studies, electrophysiological recordings, and molecular neurobiology findings from the past decade. Results demonstrate that emotional processing involves distributed neural networks with specific anatomical substrates and dynamic regulatory mechanisms. The amygdala, hippocampus, anterior cingulate cortex, and prefrontal regions form interconnected circuits that process, integrate, and regulate emotional responses. Key findings reveal that neural plasticity mechanisms, including synaptic strengthening, neurogenesis, and epigenetic modifications, play crucial roles in emotional learning and memory formation. Control mechanisms involve top-down regulation from prefrontal areas, neurotransmitter systems modulation, and hormonal influences. These findings have significant implications for understanding psychiatric disorders, developing therapeutic interventions, and advancing our knowledge of human emotional experience. The study contributes to the growing body of evidence supporting the network-based approach to understanding emotional neurophysiology and provides insights into potential targets for clinical interventions.